Effects of L-Arginine Supplementation during Late Gestation on Reproductive Performance, Piglet Uniformity, Blood Profiles, and Milk Composition in High Prolific Sows - Jinsu Hong; Lin Hu Fang; Jae Hark Jeong; Yoo Yong Kim (Animals, 2020)
This study was conducted to evaluate the effects of L-arginine supplementation levels during late gestation on reproductive performance and piglet uniformity in high prolific sows. A total of 60 F1 multiparous sows (Yorkshire × Landrace), with an average body weight of 238.2 kg, were allotted to one of three treatment groups in a completely randomized design. The dietary treatments were divided by the supplementation level of arginine during the late-gestation period, from day 70 to farrowing, as follows—(1) CON: corn-soybean meal-based basal diet (Arg 0.72%), (2) Arg10: basal diet + L-Arg 0.28% (Arg 1.0%), and (3) Arg15: basal diet + L-Arg 0.79% (Arg 1.5%). The same lactation diet was provided ad libitum to sows during the lactation period. There were no significant differences in body weight and backfat thickness in sows during late-gestation and lactation. Dietary arginine levels had no significant influences on the number of total born, stillbirth, and born alive. However, increasing inclusion level of L-arginine supplementation tended to increase (p < 0.10) alive litter weight linearly, and also linearly increased (p < 0.05) the piglet weight gain and litter weight gain during the lactation period. In piglet uniformity, the standard deviation of piglet birth weight (p < 0.05) and the coefficient of variation for piglet birth weight (p < 0.10) increased linearly, as dietary arginine levels increased in the late gestation period. Increasing L-arginine supplementation to late gestating sows linearly increased (p < 0.05) the blood concentrations of arginine and ornithine at day 90 and day 110 of gestation. On the other hand, dietary arginine levels in late gestation did not affect the blood parameters related to the nitrogen utilization. Increasing dietary arginine levels for the late gestating sows did not affect the milk composition for colostrum and milk at day 21 of lactation. In conclusion, the inclusion level of arginine in the diet for late gestating sows, by up to 1.5%, could improve the alive litter weight at birth and litter weight gain during lactation, whereas the piglet uniformity at birth was decreased due to the increase of survival for fetuses with light birth weight.